Outcome of Low-Invasive Local Split-Thickness Lengthening for Iliotibial Band Friction Syndrome - Inoue, Hiroaki; Hara, Kunio; Arai, Yuji; Nakagawa, Shuji; Kan, Hiroyuki; Hino, Manabu; Fujiwara, Hiroyoshi; Kubo, Toshikazu (International Journal of Sports Medicine, 2018)
Conventional surgical methods for iliotibial band friction syndrome (ITBFS) may affect the iliotibial band (ITB), delaying return to sports activities or impeding performance. We have developed a minimally invasive method. This study retrospectively analyzed the outcomes of this procedure in individuals with ITBFS. This study included 34 knees of 31 individuals. Surgery involved lengthening the central part of the ITB by splitting it into a superficial and a deep layer, maintaining the anterior and posterior fibers immediately above the lateral epicondyle. Outcomes included time to resume sports activity, personal best times to run a 5000-m race before and after surgery, and 2-month post-surgery muscle strengths. The mean postoperative time to return to competition was 5.8 weeks. Personal best times of 5000-m race improved in 13 of 17 runners. Two months post-surgery, the mean extensor muscle strengths on the healthy and affected sides did not significantly differ nor did the flexor muscle strengths. In ITBFS, the ITB itself is normal. Lengthening the limited region of the ITB immediately above the lateral femoral epicondyle removes the cause of ITBFS, with a reduction in inflammation. This technique resulted in early return to competition without degrading performance.
Keywords: iliotibial band; sports disorder; return to competition; surgery